Simultaneous confinement of low-energy electrons and positrons in a compact magnetic mirror trap - H Higaki; C Kaga; K Fukushima; H Okamoto; Y Nagata; Y Kanai; Y Yamazaki (New Journal of Physics, 2017)
More than 10 ^7 electrons and 10 ^5 positrons with energy less than a few eV were confined simultaneously for the first time in a compact magnetic mirror trap with plugging potentials. The exponential decay time constant of the confined positrons exceeded 70 ms at the beginning of the simultaneous confinement. Particle simulations in the early stages of the mixing process were also conducted. The results obtained in the experiments and simulations suggested that an improved setup would make it possible to investigate the unexplored field of low-energy electron–positron plasmas experimentally.